P262 New faecal calprotectin cut-off points for remission and active disease defined by UCEIS and Nancy indices in ulcerative colitis (UC). (16th January 2018) - Walsh, A; Kormilitzin, A; Hinds, C; Sexton, V; Bond, S; Wilson, J; Brain, O; Keshav, S; Uhlig, H; Geddes, J; Goodwin, G; Peters, M; et al.
Abstract: Background: Disease activity assessment is an essential part of management in UC, most accurately evaluated by endoscopy and biopsy. Most published cut-offs for faecal calprotectin (FCal) in UC are based on prediction of relapse, rather than prediction of endoscopic or histopathologic activity. Methods: The TrueColours UC pilot collected daily symptoms (simple clinical colitis activity index, SCCAI), monthly FCal (IBDoc), and endoscopic/histopathological activity (UCEIS and Nancy indices) at two time points over 6 months. Correlations between FCal (g/g), SCCAI (median of measurements for 5 days prior to FCal), UCEIS (range 0–8, within 14 days of FCal) and Nancy indices were computed by repeated measurements correlations (rmcorr) in the R package. Definitions of remission and active disease remain debated, so two groups were created. Group A defined remission as UCEIS 0 AND Nancy 0, and active disease as UCEIS 4 AND Nancy 3. Group B defined remission as UCEIS 1 AND Nancy 1, and active disease as UCEIS 4 AND Nancy 3. Mann–Whitney U test was applied to values of FCal to estimate statistical significance. Results: The number of times that a correlation could be made between FCal and other indices was termed 'number of instances' (Table 1). There was poor correlation between FCal and SCCAI (rmcorr 0.311), but good correlation with UCEIS and Nancy indices (Table 1). The distributions of FCal values for the combined UCEIS AND Nancy criteria (Figure 1) show highly significant ( p < 0.0001) discrimination by FCal between endoscopic and histologically defined remission and active disease in both groups. FCal cut offs for remission were <147 g/g (UCEIS 0 AND Nancy 0) and 180 g/g (UCEIS 1 AND Nancy 1, Table 2). Conclusions: An FCal <180 g/g is indicative of endoscopic and histological remission. FCal may act as a reliable marker of mucosal healing, replacing the need for endoscopy in some patients.